Hydrogel Electrolytes-Based Rechargeable Zinc-Ion Batteries under Harsh Conditions - Zhaoxi Shen; Zicheng Zhai; Yu Liu; Xuewei Bao; Yuechong Zhu; Tong Zhang; Linsen Li; Guo Hong; Ning Zhang (Nano-Micro Letters)
Highlights The developing history and recent advances of hydrogel electrolytes for rechargeable zinc-ion batteries under harsh conditions are summarized. The fundamentals, species, and mechanisms of the hydrogel electrolytes are discussed. The functional design strategies for advanced hydrogel electrolytes under harsh conditions are discussed. The remaining challenges and future perspectives for the practical application of hydrogel electrolyte-based rechargeable zinc-ion batteries are discussed.